EVALUASI PROSEDUR PEMUNGUTAN DAN PENERAPAN AKUNTANSI PAJAK HOTEL PADA BIG FISH HOTEL MANADO - Rotinsulu, Glenn; Sabijono, Harijanto; Walandouw, Stanley Kho (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
In increasing the number of members in tax revenue, the government is always trying to find objects of taxes that can contribute to the achievement of tax revenue. Hotel tax is one part of local taxes that have the potential to continue to grow along with support issues such as services, development and tourism in regional development policies. This study aims to evaluate the procedure of collection and application of hotel tax accounting conducted at Big Fish Hotel Manado. The type of research used in this study is descriptive qualitative research. The results of this study indicate that the implementation of hotel tax collection procedure at Big Fish Hotel Manado is in accordance with Manado City Local Regulation Number 2 Year 2011 on Regional Tax and for hotel tax accounting record has been in accordance with Statement of Financial Accounting Standards (PSAK) No. 23 on Revenue.Keywords : hotel tax collection, hotel tax accounting, local tax, PSAK No. 23